Building the framework of local Adiwiyata schools in Sintang District, West Kalimantan Province - Hendra Setiawan; Rachmi Afriani; Maria Delfina Dhae (University of Muhammadiyah Malang, 2019)
The suitable framework will enable schools to perform Adiwiyata in the best way based on their local potentials. The aim of this research was to get better knowledge about the conditions of schools awarded Adiwiyata as well as to analyze the specific strategies to create sustainabledevelopment of those Adiwiyata schools in Sintang district. This qualitative descriptive researchusedpurposive sampling technique in which the participants were SDN 7 Sintang, SMPN 3 Sungai Tebelian, and MTsN Sintang. The data was collected through questionnaire, in-depth interview, and field observation. The data gained were analized using SWOT. The results indicated that the all Adiwiyata schools achieved outstanding scores (73.15 for SDN 7 Sintang,70.40 for SMPN 3 Sungai Tebelian, and 68.13 forMTsN Sintang). Based on the SWOT analysis, the specific strategies to develop Adiwiyata schools in Sintang district were by utilizing of local unique including planting local plants, developing local culture and tradition on mutual collaboration with surrounding community, and increasing partnership with environmental agencies and the other third parties in building human resources who were reliable in maintaining environmental school program.